Expression Library Immunization Can Confer Protection against Lethal Challenge with African Swine Fever Virus - Lacasta, Anna; Ballester, María; Monteagudo, Paula L.; Rodríguez, Javier M.; Salas, María L.; Accensi, Francesc; Pina-Pedrero, Sonia; Bensaid, Albert; Argilaguet, Jordi; López Soria, Sergio; Hutet, Evelyne; Le Potier, Marie-Frédérique; et al. (American Society for Microbiology, 2014)
African swine fever is one of the most devastating pig diseases, against which there is no vaccine available. Recent work from our laboratory has demonstrated the protective potential of DNA vaccines encoding three African swine fever viral antigens (p54, p30, and the hemagglutinin extracellular domain) fused to ubiquitin. Partial protection was afforded in the absence of detectable antibodies prior to virus challenge, and survival correlated with the presence of a large number of hemagglutinin-specific CD8 + T cells in blood. Aiming to demonstrate the presence of additional CD8 + T-cell determinants with protective potential, an expression library containing more than 4,000 individual plasmid clones was constructed, each one randomly containing a Sau3AI restriction fragment of the viral genome (p54, p30, and hemagglutinin open reading frames [ORFs] excluded) fused to ubiquitin. Immunization of farm pigs with the expression library yielded 60% protection against lethal challenge with the virulent E75 strain. These results were further confirmed by using specific-pathogen-free pigs after challenging them with 10 4 hemadsorbing units (HAU) of the cell culture-adapted strain E75CV1. On this occasion, 50% of the vaccinated pigs survived the lethal challenge, and 2 out of the 8 immunized pigs showed no viremia or viral excretion at any time postinfection. In all cases, protection was afforded in the absence of detectable specific antibodies prior to challenge and correlated with the detection of specific T-cell responses at the time of sacrifice. In summary, our results clearly demonstrate the presence of additional protective determinants within the African swine fever virus (ASFV) genome and open up the possibility for their future identification.IMPORTANCE African swine fever is a highly contagious disease of domestic and wild pigs that is endemic in many sub-Saharan countries, where it causes important economic losses and is currently in continuous expansion across Europe. Unfortunately, there is no treatment nor an available vaccine. Early attempts using attenuated vaccines demonstrated their potential to protect pigs against experimental infection. However, their use in the field remains controversial due to safety issues. Although inactive and subunit vaccines did not confer solid protection against experimental ASFV infection, our DNA vaccination results have generated new expectations, confirming the key role of T-cell responses in protection and the existence of multiple ASFV antigens with protective potential, more of which are currently being identified. Thus, the future might bring complex and safe formulations containing more than a single viral determinant to obtain broadly protective vaccines. We believe that obtaining the optimal vaccine formulation it is just a matter of time, investment, and willingness.